YELLOWFIN TUNA (Thunnus albacares) FISHERIES SUSTAINABILITY: A WEIGHT-LENGTH ANALYSIS IN THE WEST SUMATERA WATERS - Emma Suri Yanti Siregar; Domu Simbolon; Ronny Irawan Wahju; Irfan Yulianto; Vincentius P. Siregar (Jurnal Teknologi Perikanan dan Kelautan)
Yellowfin tuna is a high-value fishery commodity and the primary source of livelihood for fishers in West Sumatra. However, fishing intensification often overlooks the selectivity of fishing gear, resulting in the capture of fish that are not yet suitable for fishing, which disrupts population regeneration, reduces biomass, and increases the risk of overfishing. Information on suitable catch size is important to support fisheries sustainability. This study aims to determine the distribution of fish length growth patterns and assess the catchability level of tuna (Thunnus albacares). Fish length and weight were collected by measuring tuna catches. Fish length and weight distribution were analyzed descriptively, while fish growth patterns were determined using the equation W = aLb. The study shows that the tuna measured from June to August 2020 reached 398 individuals. In addition, the dominant fish caught ranged from 135 to 144 cm and between 44 and 60 kg. The analysis of fish distribution produced a regression equation y = 0.00005x2.7787, with an R² value of 0.9575 and a b value of 2.4969, which indicates a negative allometric growth pattern, indicating that growth in fish length is more dominant than its weight growth. The results of this study indicate that 81% of tuna meet the criteria for catchability, while the others are unsuitable for catchability. This study was important in supporting the sustainable management of yellowfin tuna fisheries based on catchability size.